Survey data on strategic alignment in multispecialty hospitals: Implementing a balanced scorecard approach for optimal performanceMendeley Data - Shefali Mohan; Rohit Kushwaha; M. Venkatesan; Ramya Singh; Manish Mishra (Data in Brief)
This dataset investigates the relationship between Strategic Alignment, Balanced Scorecard (BSC), and Optimal Performance (OP) in multispecialty hospitals. Data were collected using a cross-sectional design from 530 healthcare professionals in four cities in India: Lucknow, Varanasi, Kanpur, and Prayagraj. The data collection process involved Interviews and administering structured questionnaires to participants, capturing their perceptions and experiences related to strategic alignment, BSC implementation, and performance outcomes.The dataset comprises responses from a diverse group of healthcare professionals, including doctors, nurses, administrators, and support staff. Variables in the dataset include demographic information, measures of strategic alignment, BSC implementation metrics, and performance indicators. Sentiment analysis and Descriptive statistics were used to analyze the data, Correlation and regression analyses were employed to explore the relationships between the constructs.This dataset offers significant reuse potential for researchers interested in examining strategic management practices in healthcare settings. It provides a comprehensive snapshot of how strategic alignment and performance measurement frameworks are perceived and implemented across multiple hospitals in different urban regions. The dataset can be leveraged for comparative studies, validation of performance measurement tools, and further exploration of factors influencing optimal performance in healthcare organizations.